PEMBUATAN FILM ANIMASI 2D GUNA PENGENALAN SILA DALAM PANCASILA - Arifin, Yandi; Dzikri, Afdhol (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2020)
Knowledge about Garuda Pancasila as a symbol of the Republic of Indonesia is very necessary to be learned as early as possible. Various learning methods have been used in order to introduce the Garuda Pancasila to the community, especially elementary school students. But sometimes these methods make students feel bored quickly so they are not serious in carrying out the learning process. Therefore, we need media that can entertain and provide education to the students. By using 2D animation, it is expected that the learning process can be conveyed in a more fun and enjoyable way. For this reason, a 2D animation film was made as a learning medium to introduce the symbol of the country. The process of making this 2D animated film becomes more focused by using the Godfrey method. A method of testing in the form of a survey was conducted to elementary school students about messages conveyed in the 2D animated film. The results of the test proved that the film is an effective learning medium to convey the moral messages about the importance of knowing the symbol of the country and the values ​​contained therein for children.